Railway vehicle optimisation using the concept of "Design for Control" - Christopher Ward; Tian Xiang Mei; Peter Hubbard; M. Mirzapour (2014)
Design for control is an axiom extensively used in the aerospace and automotive industries that has proven highly beneficial both in terms of performance benefits but also in reducing unit costs and reducing maintenance burdens. To date, in the railway industry, active control for vehicle suspensions has been used in a sparse manner operationally, and generally only as a performance improvement measure for essentially passive systems. There is a lack of in-depth understanding of the broader benefits for both vehicle design or architecture and extended impact on rail infrastructure that could be brought about by this concept of design for control. This paper presents a brief summary of the outcomes of a short study into the accumulative benefits of design for control if applied to future railway vehicles. The aim of the project was to determine a philosophy of vehicle architecture that would maximise the effect of the axiom in terms of: reduced unit purchase cost; reduced running costs; and improved overall system performance. The paper proposes an architecture for a mature mechatronic vehicle and dynamic studies show that significant reduction in track damage can be achieved with this approach. A simple understanding of the cost implications is also explored which shows that the real benefits will come from operational cost reduction rather than from unit purchase cost.